2007
DOI: 10.1111/j.1600-0420.2007.00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual dysfunctions and ocular disorders in children with developmental delay. II. Aspects of refractive errors, strabismus and contrast sensitivity

Abstract: ABSTRACT.Purpose: To evaluate the prevalence of refractive errors, strabismus and reduced contrast sensitivity in an unselected group of children with developmental delay (DD), and to propose extensions to the existing guidelines to assess the number of examinations required to optimally support children with DD. Methods: A total of 923 children with IQ £ 80, aged 4-15 years, from Copenhagen County, Denmark, were ophthalmically examined. The prevalence of refractive errors and strabismus and the presence of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 34 publications
2
35
1
1
Order By: Relevance
“…Neurological disorders have also been reported as co-occurring symptoms in children with ID. In particular, there is a 20-28 % prevalence risk of comorbid epilepsy in children with ID (Jelliffe-Pawlowski et al 2003;Morgan et al 2003;Nielsen et al 2007b;Oguni 2013). Various studies also suggested 16-56 % prevalence rate of comorbid cerebral palsy among children with ID (Jauhari et al 2012;Nielsen et al 2007b;Zhang and Ji 2005).…”
Section: Other Comorbiditiesmentioning
confidence: 91%
See 2 more Smart Citations
“…Neurological disorders have also been reported as co-occurring symptoms in children with ID. In particular, there is a 20-28 % prevalence risk of comorbid epilepsy in children with ID (Jelliffe-Pawlowski et al 2003;Morgan et al 2003;Nielsen et al 2007b;Oguni 2013). Various studies also suggested 16-56 % prevalence rate of comorbid cerebral palsy among children with ID (Jauhari et al 2012;Nielsen et al 2007b;Zhang and Ji 2005).…”
Section: Other Comorbiditiesmentioning
confidence: 91%
“…In particular, there is a 20-28 % prevalence risk of comorbid epilepsy in children with ID (Jelliffe-Pawlowski et al 2003;Morgan et al 2003;Nielsen et al 2007b;Oguni 2013). Various studies also suggested 16-56 % prevalence rate of comorbid cerebral palsy among children with ID (Jauhari et al 2012;Nielsen et al 2007b;Zhang and Ji 2005). Visual (2-27 %) and hearing problems (4-17 %) were also noted and are prevalent with children who have moderate to severe ID (Jauhari et al 2012;Nielsen et al 2007a;Nielsen et al 2007b).…”
Section: Other Comorbiditiesmentioning
confidence: 91%
See 1 more Smart Citation
“…According toAtkinson and Braddick, 3 the incidence of hyperopia of at least 3.50 D in the general population is only 5% between the age of 6-9 months, with the incidence decreasing on follow-up. Nielsen and colleagues 4 showed a higher incidence of high levels of hyperopia in children with developmental delay, with >3 D spherical equivalent in 15.3% of children with developmental delay and an even greater incidence of 21.8% in children with IQs <50. The higher prevalence of developmental delay in our patient series may be due in part to the fact that our study population is from a tertiary care center.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 254 children, 178 were cooperative for color vision testing. 13 of these (7.3%) were found to be defective in color vision with Ishihara chart. 76 children were un cooperative and were not able to perform color vision test.…”
mentioning
confidence: 99%